2015
DOI: 10.1103/physrevb.91.235320
|View full text |Cite|
|
Sign up to set email alerts
|

Third-order nonlinearity of graphene: Effects of phenomenological relaxation and finite temperature

Abstract: We investigate the effect of phenomenological relaxation parameters on the third-order optical nonlinearity of doped graphene by perturbatively solving the semiconductor Bloch equation around the Dirac points. An analytic expression for the nonlinear conductivity at zero temperature is obtained under the linear dispersion approximation. With this analytic formula as a starting point, we construct the conductivity at finite temperature and study the optical response to a laser pulse of finite duration. We illus… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
211
2
4

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 193 publications
(227 citation statements)
references
References 59 publications
10
211
2
4
Order By: Relevance
“…Currents associated with these intraband transitions undergo a strongly anharmonic motion that reflects the linear electronic dispersion in graphene and leads to a highly nonlinear response to external electromagnetic fields [9][10][11][12][13][14][15][16][17]. However, most experimental studies on graphene nonlinear optics have dealt with interband effects, including reports of large third-order susceptibilities linked to wave mixing [18], harmonic generation [19][20][21][22][23], and the Kerr effect [24][25][26].…”
Section: Introductionmentioning
confidence: 99%
“…Currents associated with these intraband transitions undergo a strongly anharmonic motion that reflects the linear electronic dispersion in graphene and leads to a highly nonlinear response to external electromagnetic fields [9][10][11][12][13][14][15][16][17]. However, most experimental studies on graphene nonlinear optics have dealt with interband effects, including reports of large third-order susceptibilities linked to wave mixing [18], harmonic generation [19][20][21][22][23], and the Kerr effect [24][25][26].…”
Section: Introductionmentioning
confidence: 99%
“…Two-color photocurrents have been observed [7], and the expressions for the nonlinear optical response that describes them have been worked out in detail [8] for frequencies where states near the K points are important, with scattering included phenomenologically.Unlike most semiconductors, where two-color injection currents have been studied forhω < E g < 2hω, in undoped graphene one-photon absorption is possible at both 2ω and ω, and so complexities in the injected currents arise [9]. Yet since the lattice structure has inversion symmetry there are no one-color effects.…”
Section: Introductionmentioning
confidence: 99%
“…Ooi et al [111] substituted the full expression of the linear susceptibility, which includes the electronic scattering frequencies, and found that graphene may exhibit negative nonlinear refraction for certain E F values and wavelengths. Subsequent Bloch derivations by Cheng et al [75] also yield negative nonlinear conductivities for both the real and imaginary parts, when appropriate scattering frequencies and room temperature are applied, as shown in figure 8. Similarly, while early experimental investigations did not explicitly distinguish between the signs of graphene's nonlinear coefficient, very recent works have unanimously found negative nonlinear refractive indices in the visible and telecommunication wavelengths.…”
Section: (C) Negative Nonlinear Refractive Index Of Graphenementioning
confidence: 99%
“…However, to compare with experimental measurements, the recasting of the 2D nonlinear conductivity into the 3D nonlinear refractive index via graphene's thickness is applied, as in the case of the modelling of graphene's linear refractive index. This is prominently practised by Cheng et al [73,75,76] in several of their landmark papers on the theoretical derivations of graphene's nonlinear optical response. Quantitatively, the theoretical models predict a Kerr-type nonlinear coefficient of the order of n 2 ∼ 10 −11 -10 −13 m 2 W −1 around the visible and telecommunication wavelengths.…”
Section: Nonlinear Optical Properties Of Graphene (A) Theoretical Stumentioning
confidence: 99%
See 1 more Smart Citation